UMP Board of Director’s Chairman presented with Honorary Degree in Education Management from USM - UMP, PNC (2018)
Universiti Malaysia Pahang (UMP) Board of Director’s Chairman, Dato’ Sri Ibrahim Ahmad was presented with an Honorary Degree in Education Management by Universiti Sains Malaysia (USM) during its 56th convocation ceremony.